NON-EQUIVALENCE RELATING TO CULTURAL DIFFERENCES AT WORD LEVEL IN ENGLISH – VIETNAMESE TRANSLATION = Hiện tượng không tương đương ở cấp độ từ do những khác biệt về văn hóa trong biên dịch Anh - Việt - Nguyễn, Thị Bích Hường (2020)
Equivalence is one of the crucial issues in translation studies that have constantly received much attention of researchers since the birth of translation studies. Translation equivalence is linked to both linguistic and cultural aspects; however, in the thesis, equivalence is studied in the relation to culture. This paper attempted to discuss the importance and evaluate effects of cultural factors in the process of written translation. It was carried out into the problems of non-equivalence caused by cultural differences at word level from English into Vietnamese. In terms of its theoretical framework, the study was mainly based on Baker‟s concepts (1992) about non-equivalence at word level. In the thesis, the research method of contrastive analysis was adopted to compare and contrast distinctive cultural features between two languages. Its purpose was to evaluate the degree of translatability that target language text can achieve and the degree of untranslatability, i.e. non-equivalence, between two languages. The research outcome confirmed that non-equivalence in the English – Vietnamese translation was associated with the existence of cultural factors in the source language text. In addition, the applicability of Baker‟s classification about common problems could be found in the chapter of findings and discussion. Finally, cross-cultural knowledge between English and Vietnamese was also demonstrated.